Identification and Fine Mapping of Pi69(t), a New Gene Conferring Broad-Spectrum Resistance Against Magnaporthe oryzae From Oryza glaberrima Steud - Dong, Liying; Liu, Shufang; Kyaing, May Sandar; Xu, Peng; Tharreau, Didier; Deng, Wei; Li, Xundong; Bi, Yunqing; Zeng, Li; Li, Jing; Zhou, Jiawu; Tao, Dayun; et al. (Frontiers in Plant Science, 2020)
The discovery and deployment of new broad-spectrum resistance (R) genes from cultivated rice and its wild relatives is a strategy to broaden the genetic basis of modern rice cultivars to combat rice blast disease. Oryza glaberrima possessing many valuable traits for tolerance to biotic and abiotic stresses, is an elite gene pool for improvement of Asian cultivated rice. An introgression line IL106 derived from O. glaberrima (Acc. IRGC100137) confers complete resistance to Magnaporthe oryzae in blast nursery. Genetic analysis using 2185 BC6F2 progenies derived from a cross between IL106 and the recurrent parent Dianjingyou 1 showed that IL106 harbors a single dominant resistance gene against M. oryzae strain 09BSH-10-5A. This gene was preliminarily mapped on the long arm of chromosome 6 of rice in a region of ca. 0.9 cM delimited by two SSR markers (RM20650 and RM20701). In order to finely map this gene, 17,100 additional progenies were further analyzed. As a result, this gene was further narrowed down to a region flanked by two molecular markers STS69-15 and STS69-7, and co-segregated with 3 molecular markers, RM20676, STS69-21 and STS69-22 on the long arm of chromosome 6. Based on reference genome sequences, this R gene was mapped in silico in 76.1-Kb and 67.7-Kb physical intervals, and containing 4 and 3 NBS-LRR candidate genes in O. sativa cultivar Nipponbare and O. glaberrima cultivar CG14, respectively. Because no blast resistance gene was finely mapped in this physical interval before, this R gene was considered as not described yet and designated as Pi69(t), which is the first identified and finely mapped blast R gene from O. glaberrima, as far as we know. Evaluation of IL106 with 151 blast strains collected from 6 countries in Asia showed that 148 strains are avirulent on IL106, suggesting that Pi69(t) is a broad-spectrum blast R gene, and a promising resistant resource for improvement of Asian cultivated rice.